Activated Peripheral Blood B Cells in Rheumatoid Arthritis and Their Relationship to Anti–Tumor Necrosis Factor Treatment and Response: A Randomized Clinical Trial of the Effects of Anti–Tumor Necrosis Factor on B Cells. Issue 2 (27th December 2021) - Meednu, Nida; Barnard, Jennifer; Callahan, Kelly; Coca, Andreea; Marston, Bethany; Thiele, Ralf; Tabechian, Darren; Bolster, Marcy; Curtis, Jeffrey; Mackay, Meggan; Graf, Jonathan; Keating, Richard; et al.
Abstract : Objective: B cells can become activated in germinal center (GC) reactions in secondary lymphoid tissue and in ectopic GCs in rheumatoid arthritis (RA) synovium that may be tumor necrosis factor (TNF) and lymphotoxin (LT) dependent. This study was undertaken to characterize the peripheral B cell compartment longitudinally during anti‐TNF therapy in RA. Methods: Participants were randomized in a 2:1 ratio to receive standard dosing regimens of etanercept (n = 43) or adalimumab (n = 20) for 24 weeks. Eligible participants met the American College of Rheumatology 1987 criteria for RA, had clinically active disease (Disease Activity Score in 28 joints >4.4), and were receiving stable doses of methotrexate. The primary mechanistic end point was the change in switched memory B cell fraction from baseline to week 12 in each treatment group. Results: B cell subsets remained surprisingly stable over the course of the study regardless of treatment group, with no significant change in memory B cells. Blockade of TNF and LT with etanercept compared to blockade of TNF alone with adalimumab did not translate into significant differences in clinical response. The frequencies of multiple activated B cell populations, including CD21− double‐negative memory and activated naive B cells, were higher in RA nonresponders at all time points, and CD95+ activated B cell frequencies were increased in patients receiving anti‐TNF treatment in the nonresponder group. In contrast, frequencies of transitional B cells—a putative regulatory subset—were lower in the nonresponders. Conclusion: Overall, our results support the notion that peripheral blood B cell subsets are remarkably stable in RA and not differentially impacted by dual blockade of TNF and LT with etanercept or single blockade of TNF with adalimumab. Activated B cells do associate with a less robust response.